Prediction of Prolonged Postoperative Ileus After Radical Gastrectomy for Gastric Cancer: A Scoring System Obtained From a Prospective Study. Issue 51 (December 2015) - Huang, Dong-Dong; Zhuang, Cheng-Le; Wang, Su-Lin; Pang, Wen-Yang; Lou, Neng; Zhou, Chong-Jun; Chen, Fan-Feng; Shen, Xian; Yu, Zhen
Abstract : Abstract: Currently, there is a paucity of study investigating postoperative ileus in gastric cancer surgery. This prospective study aims to identify the risk factors for prolonged postoperative ileus (PPOI) and to use these risk factors to generate a risk stratification scoring system for the occurrence of PPOI. Patients who underwent radical gastrectomy for gastric cancer were included in this study. A multivariate logistic analysis was applied to identify independent risk factors for PPOI and to generate the scoring system. A receiver operating characteristic curve was generated and the area under the curve was calculated to demonstrate the predictive power of the scoring system. Finally, 296 patients were included and analyzed, of whom 96 (32.4%) developed PPOI. The multivariate analysis showed that age ≥65 years, operative duration ≥4 hours, tumor–node–metastasis (TNM) stage = III, open/converted operative technique, and total postoperative opiates dose (TOD) ≥0.3 mg/kg were independent risk factors for PPOI. Based on these factors, a risk stratification scoring system was generated, classified by low-risk (score 0–2), moderate-risk (score 3–4), and high-risk (score 5–6) groups. The incidence of PPOI increased by 7.5-fold from low-risk to high-risk group. The area under the curve of the scoring system was 0.841 (95% CI, 0.793–0.890), indicating a good predictive capability for the occurrence of PPOI. We have identified independent risk factors for the occurrence of PPOI and used these factors to construct a risk stratification scoring system. Abstract : Supplemental Digital Content is available in the text